PHILLIPSITE MINERAL IN DEEP SEA SEDIMENT FROM SINGLE CORE IN ROO RISE, INDIAN OCEAN - MIMIN K. ADISAPUTRA; HARTONO HARTONO (Indonesian Mining Journal, 2007)
During the MD III - IMAGES IV Expedition, one of the cores that has length around 30.30 m below sea floor (bsf) was obtained using gigantic piston corer from the depth of 3,884 m below sea level (bsl). This core (MD982156) is located in Roo Rise, Indian Ocean, south of East Jawa, outer part of Jawa Trench. The sediment consists of abundance planktonic foraminifera in the upper part while in the lower part, there is no planktonic one. The latter is mostly composed of phillipsite-rich sediment (± 40%) that is possibly derived from tephra. The base of the core between the depths of 30 – 30.30 m bsf is composed of clay sediment, consisting of minerals derived from zeolite group (phillipsite), gibbsite, and other cryptocrystalline masses. Phillipsite was deposited as an authigenic deep sea sediment, whereas gibbsite is usually deposited within bodies of water. Besides, there are also nanno- plankton accumulated in the crystal of phillipsite. This part has an age of Late Miocene or older. This fact is supported by the overlain layer containing planktonic foraminifera species Sphaeroidinellopsis seminulina of Late Miocene age (N17). The thickness and the lateral continuity of this layer are still unknown.